Identification of Forestland as Envisaged in the Forest Conservation Act - Bahuguna, N. C. (Indian Forester, 2007)
The Apex Court has clarified that with a view to check deforestation, the word ’forestland’ occurring in section 2 of Forest Conservation Act, 1980 will include ’forest’ in dictionary sense in addition to recorded forest irrespective or ownership or classification thereof. Most of the States could, however, not define the ’forest’ in dictionary sense due to confusion about minimum vegetation density and minimum areas for consideration. For proper application of FCA, ecological consideration should also be given due weightage. Small areas should be excluded from the definition of forest unless there are rare and endangered flora and fauna. Large wilderness areas, devoid of trees, which are free from human interference, should be considered forest. The areas between 1.0ha with density 1.0 and 100ha with density zero should be treated as forest. The values in between could be calibrated on the basis of exponential decrease in density. Plantations raised on non-forestlands should not be treated as forest.